Embracing conceptual diversity to integrate power and institutional analysis: Introducing a relational typology. Issue 2 (August 2018) - Bennett, Abigail; Acton, Leslie; Epstein, Graham; Gruby, Rebecca L.; Nenadovic, Mateja
Within environmental governance scholarship, an increasing interest in integrating the study of power with institutional analysis is generating novel theoretical and empirical perspectives for understanding human-environment relationships. The array of different approaches employed to integrate power into institutionalist work promises a range of insights. However, building a cohesive research agenda depends on efforts to grapple with the conceptual and theoretical diversity that characterizes the study of power. To this end, we introduce a typology of relationships between power and institutions. The typology brings together diverse conceptualizations of power and institutions within a common analytical space and situates them around two overarching research questions: How does power shape institutions? And how do institutions shape power? The structure of the typology aids researchers in generating specific, operationalizable research questions within the broader research agenda on power and institutions. In the paper, we describe the theoretical basis for the development of the typology, which draws on political ecology and Bloomington School institutionalism. Then, we employ the typology to organize a review of environmental governance literature on power and institutions. This exercise demonstrates the utility of the typology not only for organizing the currently disjointed body of work on power and institutions but also for identifying new research questions. Furthermore, it facilitates discussions about deeper ontological, epistemological, and methodological challenges associated with bringing together different theoretical approaches. Ultimately, the typology defines pathways for integrating two important disciplines studying environmental governance, political ecology and institutionalism, and facilitates the accumulation of a coherent body of knowledge.